IMMUNE INDEXES OF PERIPHERAL BLOOD IN ELDERLY WOMEN DURING ACCELERATION EXERCISE (WHOLE BODY VIBRATION): A PILOT TWELVE-WEEK TRIAL - V. F. Pyatin; I. V. Shirolapov; A. V. Zhestkov; O. L. Nikitin; L. V. Limareva; I. A. Zubova (Медицинская иммунология)
Effects of a 12-week acceleration exercise program (whole body vibration) were studied in 39 elderly women. Immune cell subsets, expression of lymphocyte activation markers, levels of pro-inflammatory serum cytokines (IL-8 and TNFα), and serum immunoglobulins (A, M, G) were evaluated. It has been revealed that the progression-based acceleration training is not a sufficient stress factor affecting immune functions, and it does not produce any significant postexercise suppression of immune functions in elderly women.